2021
DOI: 10.3390/universe7060188
|View full text |Cite
|
Sign up to set email alerts
|

Jet-Induced Feedback in the [O III] Lines of Early Evolution Stage Active Galactic Nuclei

Abstract: It is well known that active galactic nuclei (AGN) show various forms of interaction with their host galaxy, in a number of phenomena generally called AGN feedback. In particular, the relativistic plasma jets launched by a fraction of AGN can strongly affect their environment. We present here a study of the [O III] λλ4959,5007 lines in a diverse sample of early evolution stage AGN–specifically narrow-line Seyfert 1 galaxies. Radio imaging observations of all of the sources enable a division to jetted and non-j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 119 publications
(168 reference statements)
0
5
0
Order By: Relevance
“…Several studies have found a connection between the level of radio emission in AGN host galaxies and the presence of ionised outflows (Mullaney et al 2013;Zakamska & Greene 2014;Molyneux et al 2019;Jarvis et al 2021). Also, observational evidence has been reported that suggests outflow kinematics and radio jets are related (Smirnova et al 2007;Nesvadba et al 2017;Berton & Järvelä 2021). However, Wang et al (2018) found no connection between the radio properties and the outflow kinematics.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found a connection between the level of radio emission in AGN host galaxies and the presence of ionised outflows (Mullaney et al 2013;Zakamska & Greene 2014;Molyneux et al 2019;Jarvis et al 2021). Also, observational evidence has been reported that suggests outflow kinematics and radio jets are related (Smirnova et al 2007;Nesvadba et al 2017;Berton & Järvelä 2021). However, Wang et al (2018) found no connection between the radio properties and the outflow kinematics.…”
Section: Introductionmentioning
confidence: 99%
“…At low-z, only in the case of the 'blue-outliers' the [O iii]λλ4959,5007 profiles appear to be very boxy-shaped and with the FWHM > 1000 km s −1 . Some of these sources are NLSy1s and the [O iii]λλ4959,5007 FWHM is becoming comparable to the one of the broad Hβ profile sources (Zamanov et al 2002;Komossa et al 2008;Cracco et al 2016;Komossa et al 2018;Berton & Järvelä 2021). At high z and high luminosity the [O iii]λλ4959,5007 profiles often appear much broader, as do also the Hβ broad profiles (Carniani et al 2015;Fiore et al 2017;Villar Martín et al 2020).…”
Section: Hβ and [O Iii]λλ49595007mentioning
confidence: 95%
“…High-ionisation lines like [O iii]λλ4959,5007 are seen as one of the main detectors of outflowing gas in radio-quiet sources (Zamanov et al 2002;Komossa et al 2008;Zhang et al 2011;Marziani et al 2016b). In the case of radio-loud sources, narrowline outflowing gas has been associated with jets through the blueshifted line components (Capetti et al 1996;Axon et al 2000;Bicknell 2002;Kauffmann et al 2008;Best & Heckman 2012;Reynaldi & Feinstein 2013;Jarvis et al 2019;Berton & Järvelä 2021). Outflows are also detected in Hβ.…”
Section: [O Iii]λλ4959 5007mentioning
confidence: 99%
“…Narrow-line Seyfert 1 galaxies can also have blueshifted line profiles, which is indicative of outflows, though this is mostly in high-ionisation lines (e.g. Zamanov et al 2002;Boroson 2005;Berton & Järvelä 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a relativistic jet with high inclination with respect to the line of sight can be weak due to the lack of relativistic boosting, leading to a wrong classification. Finally, a population of relativistic radio jets, almost totally absorbed at low radio frequencies and thus deemed radio-silent or -quiet, has recently emerged Berton & Järvelä 2021). These issues with the radio-loudness remain true even at high redshifts (Sbarrato et al 2021).…”
Section: Introductionmentioning
confidence: 99%